Sustainable Energy Development Using Space-Based Solar Power in Indian context - Bhagat, Meghna; Joy, Rosewine (Quest Journal of Management and Social Sciences, 2021)
Background: Progressive degradation of the environment due to the intervention of humans in the natural processes brought into light the need and the concept of sustainable development. The three pillars of sustainable development are Economic, Social, and Environmental. Sustainability has become one of the important tools to overcome the threats and is the dire need of the hour. This paper illustrates the detailed concept of Space-based solar power (SBSP) which defines the collection of solar energy in outer space and directing it towards the earth using electromagnetic waves. The edge of collecting solar power from space and not by the conventional methods include the strong collection rate and improved collection period. This is mainly because of the absence of the earth’s atmosphere that consists of a lot of external impurities and the decreased effects of reflection and absorption on solar energy on its way to earth. Objective: To put forward the importance of the use of space-based solar power system in India and to establish how space-based solar power is one of the answers of sustainable energy development for a better future for the country. Method: The study is based on secondary data. The findings indicate the need for sustainable energy development and the effective use of space-based solar power which would answer to the never-ending demands of human beings. Result: The article also delineates the opportunities of space-based solar power as well as the challenges that might be faced while building the system. Conclusion: The paper is a descriptive and conceptual study which illustrates SBSP as an innovative and important breakthrough in the field of science and one of the most important topics of discussion that needs to be addressed. The paper suggests the need for conducting more study on the topic and development of projects to measure its feasibility in the future, in terms of Indian context.